2009
DOI: 10.1152/ajpheart.00462.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine regulation of microtubule dynamics in cardiac hypertrophy

Abstract: There is evidence that endogenous extracellular adenosine reduces cardiac hypertrophy and heart failure in mice subjected to chronic pressure overload, but the mechanism by which adenosine exerts these protective effects is unknown. Here, we identified a novel role for adenosine in regulation of the cardiac microtubule cytoskeleton that may contribute to its beneficial effects in the overloaded heart. In neonatal cardiomyocytes, phenylephrine promoted hypertrophy and reorganization of the cytoskeleton, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 63 publications
8
34
0
Order By: Relevance
“…In support of a role for MT accumulation in contractile dysfunction in AMPK KO mice, we observed that polymerized microtubule levels correlated strikingly with reduced left ventricular ejection fraction and pulmonary congestion in mice exposed to TAC. Furthermore, our previous study demonstrated that periodic colchicine treatment attenuated chamber dilation and improved contractile function in Balb-c mice exposed to pressure overload (7). The present data suggest that agents that activate AMPK may similarly preserve contractile function by preventing MT densification.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In support of a role for MT accumulation in contractile dysfunction in AMPK KO mice, we observed that polymerized microtubule levels correlated strikingly with reduced left ventricular ejection fraction and pulmonary congestion in mice exposed to TAC. Furthermore, our previous study demonstrated that periodic colchicine treatment attenuated chamber dilation and improved contractile function in Balb-c mice exposed to pressure overload (7). The present data suggest that agents that activate AMPK may similarly preserve contractile function by preventing MT densification.…”
Section: Discussionsupporting
confidence: 68%
“…Neonatal rat ventricular cardiomyocytes (NRVMs) were isolated from 2-day-old Sprague-Dawley rats by enzymatic digestion and separated from nonmuscle cells on a discontinuous Percoll gradient. NRVMs were isolated from 2-day-old Sprague-Dawley rats by enzymatic digestion and separated from nonmuscle cells on a discontinuous Percoll gradient, as previously described (7). A total of 2-4 million viable myocytes were isolated per ventricle with very little fibroblast contamination (Ͻ2%) and plated on gelatin-coated plates in serum-containing DMEM (0.5-1 ϫ 10 5 cells/cm 2 ) and incubated for 48 h to allow attachment and spreading, after which, the medium was replaced with serum-free media for 24 h prior to treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that increased ␤-adrenergic activity is regularly seen in pathological cardiac hypertrophy, including this model of severe RV pressure overloading (14), together with the recent observation that ␤-adrenergic agonists cause Pak1 activation (33), and that adenosine inhibits the cardiac hypertrophy-dependent microtubule changes (19), likely through its antiadrenergic effects (12), led to the present study; that is, in the setting of this knowledge, we hypothesized and then showed here that chronic ␤-adrenergic blockade would prevent the abnormal microtubule network from forming during pathological cardiac hypertrophy.…”
Section: Does Increased ␤-Adrenergic Activity Reproduce the Signalingmentioning
confidence: 76%
“…As MT reorganization is specifically linked to cardiac hypertrophy associated with contractile dysfunction (13, 37), our findings suggest that stable MTs could be promoted in the absence or down-regulation of ERK activity and is consistent with ERK function in promoting cardiac hypertrophy without contractile deficits. One complication arises with the recent study reporting modest elevation of glu-tubulin levels in PEtreated neonatal cardiac myocytes, although this study did not investigate effects of other hypertrophic stimuli such as the IL6 family of cytokines or the specific role for the ERK MAPKs (35).…”
Section: Discussionmentioning
confidence: 99%